Phenotypic and Molecular Heterogeneity in Mandibulofacial Dysostoses: A Case Series From India. (November 2022) - Shenoy, Rathika D.; Shetty, Vikram; Dheedene, Annelies; Menten, Björn; Pandyanda Nanjappa, Dechamma; Chakraborty, Gunimala; Sips, Patrick; de Paepe, Anne; Callewaert, Bert; Chakraborty, Anirban
Objective: Facial dysostosis is a group of rare craniofacial congenital disabilities requiring multidisciplinary long-term care. This report presents the phenotypic and genotypic information from South India. Design: The study is a case series. Setting: This was an international collaborative study involving a tertiary craniofacial clinic and medical genetics unit. Patients, Participants: The participants were 9 families with 17 affected individuals of facial dysostosis. Intervention: Exome analysis focused on known genes associated with acrofacial and mandibulofacial syndromes. Main Outcome Measure: The outcome measure was to report phenotyptic and genetic heterogeneity in affected individuals. Results: A Tessier cleft was seen in 7 (41%), lower eyelid coloboma in 12 (65%), ear anomalies in 10 (59%), uniolateral or bilateral aural atresia in 4 (24%), and deafness in 6 (35%). The facial gestalt of Treacher Collins syndrome (TCS) showed extensive phenotypic variations. Pathogenic variants in TCOF1 (Treacher Collins syndrome) were seen in six families, POLR1A (acrofacial dysostosis, Cincinnati type) and EFTUD2 (mandibulofacial dysostosis with microcephaly) in one each. One family (11.1%) had no detectable variation. Five out of six probands with Treacher Collins syndrome had other affected family members (83.3%), including a non-penetrant mother, identified after sequencing. Conclusion: Our report illustrates the molecular heterogeneity of mandibulofacial dysostosis in India.